Oral Presentations Abstracts: ALLOCATING RESOURCES IN CANCER CARE DURING PANDEMIC. FINDINGS FROM A QUALITATIVE INTERVIEW STUDY WITH ONCOLOGISTS AND ETHICAL ANALYSIS - SOMMERLATTE, Sabine; KRAEFT, Anna-Lena; LUGNIER, Celine; REINACHER-SCHICK, Anke; SCHILDMANN, Jan (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Allocation of health resources towards the treatment of patients with COVID-19 may affect the quality of care for non-COVID-19 patients. Several medical societies representing cancer health professionals have issued statements on priority setting in cancer care in the wake of the Sars-CoV-2 outbreak (1, 2). However, there is a lack of empirical data on how resources are prioritized in cancer care and which criteria are taken into consideration by those involved in decision making. In this paper we will present findings from qualitative interviews conducted with oncologists in Germany between February and July 2021. Transcripts of interviews are analysed following principles of qualitative content analysis based on Kuckartz (3). According to preliminary analysis of the first five interviews conducted three major topics emerge: Experiences with scarcity regarding selected diagnostic procedures and treatment. Material and procedural criteria for priority setting and decisions on deviations of standards of care. Effects of priority setting on coping and psycho-social support. We will discuss findings with regards to their possible contribution to an empirical and normative founded guidance for priority setting in cancer care in times of Sars-CoV-2 outbreak and comparable events.